Сhemical Melioration The Solving Problem Of Soil Degradation In Eastern Podillia - Dedov, A. V. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2014)
The degradation reasons of Eastern Podillia soils are investigated, their agro-ecological condition and the necessity improvement by the help of the chemical melioration are graunded in the article. Termination of soil degradation requires urgent adoption of a set of organizational, technological and fiscal measures to the deoxidation of land and increase its scale, using existing local limestone.